2013
DOI: 10.1002/srin.201300197
|View full text |Cite
|
Sign up to set email alerts
|

Study on Direct Reduction of Hematite Pellets Using a New TG Setup

Abstract: A new thermogravimetric setup was developed to study direct reduction of iron oxide under well‐controlled experimental conditions. Pure and industrial hematite samples were isothermally reduced by hydrogen and carbon monoxide gaseous mixtures. Influences of gas composition, gas flow rate, and temperature on reduction were investigated. Reduction rates obtained using the new setup were higher compared to conventional thermogravimetric method. This difference was due to the time required to replace the inert gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 18 publications
1
42
1
Order By: Relevance
“…Similar results were obtained and discussed in the previous work. [11] Carbon deposition during reduction has been reported in other works which used gas mixtures containing H 2 and CO. [1,2,6,7,9] Formation of graphite takes place on the surface of pellets in atmospheres with high carbon potential. Reduced iron acts as a catalyst for carbon deposition; therefore, the amount of deposited carbon is enhanced as reduction proceeds.…”
Section: A Effect Of Reaction Temperaturementioning
confidence: 89%
See 3 more Smart Citations
“…Similar results were obtained and discussed in the previous work. [11] Carbon deposition during reduction has been reported in other works which used gas mixtures containing H 2 and CO. [1,2,6,7,9] Formation of graphite takes place on the surface of pellets in atmospheres with high carbon potential. Reduced iron acts as a catalyst for carbon deposition; therefore, the amount of deposited carbon is enhanced as reduction proceeds.…”
Section: A Effect Of Reaction Temperaturementioning
confidence: 89%
“…Calculation of the thermodynamic activity of carbon in a gas mixture of H 2 -CO-H 2 O-CO 2 was performed previously by the authors. [11] The results showed that increasing the temperature at a fixed gas composition, and gradual increase of CO 2 (from 0.01 to 10 pct) at a constant temperature decrease the carbon activity in the gas mixture.…”
Section: B Effect Of Gas Compositionmentioning
confidence: 92%
See 2 more Smart Citations
“…DRI derives its name from the chemical change that iron ore undergoes when it is heated in a furnace at high temperatures. The reducing gas is a mixture, the majority of which is hydrogen (H 2 ) and carbon monoxide (CO) which act as reducing agents [2][3].…”
Section: Introductionmentioning
confidence: 99%